Alternative Pathway Involvement in Protoporphyria Patients Related to Sun Exposure - Granata, Francesca; Duca, Lorena; Brancaleoni, Valentina; Fustinoni, Silvia; De Luca, Giacomo; Motta, Irene; Graziadei, Giovanna; Di Pierro, Elena (Frontiers in Immunology, 2021)
The homeostasis of tissues in a chronic disease is an essential function of the alternative pathway (AP) of the complement system (CS). However, if not controlled, it may also be detrimental to healthy cells with a consequent aggravation of symptoms. The protoporphyria (PP) is a rare chronic disease that causes phototoxicity in visible light with local skin pain and general malaise. In order to establish if there is a systemic involvement of the CS during sun exposure, we designed a non-invasive method with a serum collection in winter and summer from 19 PP and 13 controls to detect the levels of CS protein: Properdin, Factor H (FH), and C5. Moreover, the global radiation data were collected from the regional agency of environmental protection (ARPA). The results show growing values for every protein in patients with PP, compared to control, in both seasons, in particular in summer compared to winter. To reinforce the evidence, we have estimated the personal exposure of patients based on the global radiation data. The main factors of the AP increased over the season, confirming the involvement of the AP in relation to light exposure. The systemic response could justify the general malaise of patients after long light exposure and can be exploited to elucidate new therapeutic approaches.